Trust based optimal routing in MANET's - Neelakandan, S; Anand, J Gokul (2011 International Conference on Emerging Trends in Electrical and Computer Technology, 2011)
MANETs are unplanned, self-organizing networks composed of mobile nodes that utilize mesh networking principles for inter-connectivity. They do not have a fixed infra-structure which makes them easy to build over an area. Mobile Ad hoc networks (MANETs) have several advantages compared to traditional wireless networks. These include ease of deployment, speed of deployment and decreased dependency on a fixed infrastructure. There have been many studies done in this area to improve the quality and efficiency of the routing protocols in MANETs. However unique characteristics of MANETs topology such as open peer-to-peer architecture, dynamic network topology, shared wireless medium and limited resource (battery, memory and computation power) pose a number of non-trivial challenges to security design. The fixed infrastructure less environment makes the transactions less secure. Traditional routing algorithms in MANETs do not work with cryptographic techniques. Cryptography procedures were introduced in them to make secure transactions. This paper proposes a secure, trusted, optimal scheme for routing in MANETs.